2014
DOI: 10.1007/s00425-014-2217-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression divergence of cellulose synthase (CesA) genes after a recent whole genome duplication event in Populus

Abstract: Secondary cell wall-associated CesA genes in Populus have undergone a functional differentiation in expression pattern that may be attributable to evolutionary alteration of regulatory modules. Gene duplication is an important mechanism for functional divergence of genes. Secondary cell wall-associated cellulose synthase genes (CesA4, CesA7 and CesA8) are duplicated in Populus plants due to a recent whole genome duplication event. Here, we demonstrate that duplicate CesA genes show tissue-dependent expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Our estimate of regulatory divergence can be considered conservative, representing cases where paralogs display distinctly different expression profiles across cambial growth and wood formation. However, the high spatial resolution of our dataset also enabled the identification of far more subtle differences, such as the previously reported differences in expression levels between CesA8-A and CesA8-B in secondary phloem and xylem (both located in cluster g, Figure 9C ( Takata and Taniguchi, 2015). While the processes of sub-, neo-or non-functionalization drives the divergence of paralog pairs, the gene dosage balance hypothesis may explain why some paralog pairs have retained similar expression profiles (Yoo et al, 2014).…”
Section: A Majority Of Paralogs Show Differential Expression During Wmentioning
confidence: 69%
See 1 more Smart Citation
“…Our estimate of regulatory divergence can be considered conservative, representing cases where paralogs display distinctly different expression profiles across cambial growth and wood formation. However, the high spatial resolution of our dataset also enabled the identification of far more subtle differences, such as the previously reported differences in expression levels between CesA8-A and CesA8-B in secondary phloem and xylem (both located in cluster g, Figure 9C ( Takata and Taniguchi, 2015). While the processes of sub-, neo-or non-functionalization drives the divergence of paralog pairs, the gene dosage balance hypothesis may explain why some paralog pairs have retained similar expression profiles (Yoo et al, 2014).…”
Section: A Majority Of Paralogs Show Differential Expression During Wmentioning
confidence: 69%
“…These may 007G098600 (cluster g)). (C) Previously published real-time PCR data of CesA genes showed that PtCesA8-B (Potri.004G059600) was expressed higher than PtCesA8-A (Potri.011G069600) in secondary phloem and xylem (Takata and Taniguchi, 2015). Although these genes have highly similar expression profiles (Pearson correlation = 0.93), and are therefore considered as conserved according to our definition (both belong to cluster g), the data confirm the difference in expression levels and show that even more subtle regulatory divergence can be detected in the dataset.…”
Section: A Majority Of Paralogs Show Differential Expression During Wmentioning
confidence: 99%
“…(C) Previously published real-time PCR data of CesA genes showed that PtCesA8-B (Potri.004G059600) was expressed higher than PtCesA8-A (Potri.011G069600) in secondary phloem and xylem (Takata and Taniguchi, 2015). Although these genes have highly similar expression profiles (Pearson correlation = 0.93) and are therefore considered as conserved according to our definition (both belong to cluster g), the data confirm the difference in expression levels and show that even more subtle regulatory divergence can be detected in the data set.…”
Section: A Majority Of Paralogs Show Differential Expression During Wmentioning
confidence: 99%
“…CesA8-A and CesA8-B in secondary phloem and xylem (both located in cluster g; Figure 8C; Takata and Taniguchi, 2015). While the processes of sub-, neo-, or nonfunctionalization drive the divergence of paralog pairs, the gene dosage balance hypothesis may explain why some paralog pairs have retained similar expression profiles (Yoo et al, 2014).…”
Section: A Majority Of Paralogs Show Differential Expression During Wmentioning
confidence: 99%
“…Moreover, three CesA genes, namely PtCesA4, PtCesA7, and PtCesA8, showed tissue-dependent expression divergence in Populus plants (Takata and Taniguchi 2015).…”
Section: Introductionmentioning
confidence: 99%